Gender differences in the fatigability of the inspiratory muscles - Gonzales, J. U.; Scheuermann, B. W. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The purpose of the present study was to determine whether gender differences are present in the fatigability of the inspiratory muscles of humans. Based on evidence for a gender difference in the oxygen cost of breathing, we hypothesized that females would result in a greater magnitude and/or faster rate of inspiratory muscle fatigue than males.